По следам пиратов Боденского озера: перевод с немецкого - Брецина Томас (Кникербокер-банда, 1992)
Экземпляры: (20180129) / Инвентарный номер: 35494 / Цена: 53.00 / Сис.шифр: И / Авт.знак: Б 87 / ББК: 84(4Авс)